Accuracy of Cone Beam Computed Tomography, Photostimulable Phosphor Plate Digital Radiography and Conventional Radiography for Detection of Artificial Cancellous Bone Defects - Roghieh Bardal Bardal; Hassan Jahanihashemi; Maryam Mostafavi; Esmaeil Kalhor; Maryam Tofangchiha; Mahdieh Dehghani (Tehran University of Medical Sciences, 2016)
Objectives: The optimal goal of radiography is to provide high-quality diagnostic images with the least patient radiation dose. The aim of this study was to evaluate the accuracy of cone-beam computed tomography (CBCT) and intraoral photostimulable phosphor plate (PSP) digital and film-based conventional radiography for detection of artificial cancellous bone defects. Materials and Methods: Five dry human mandibles were used in this study. The mandibles were placed inside a water bath made of plexiglass plates; then PSP and CBCT scans were obtained. The mandibles were cut by a coping saw in buccolingual dimension and oval defects measuring 6.1×6.1 mm, 3×6.1 mm and 4×4 mm were created by a milling machine in the spongy bone. After fixing the two parts together (buccal and lingual), radiographs were repeated. Presence or absence of defects on images was evaluated and recorded by the two observers. Using SPSS 16, compatibility level, sensitivity, specificity and receiver operating curve (ROC) analysis were determined for each observer. Results: The intraobserver agreement in all three imaging modalities was low to moderate (kappa≤0.613). The inter-observer agreement in all the three imaging modalities was moderate (kappa=0.406). The area under the curve (AUC) of the imaging modalities in each observation was not significantly different. The area under the curve based on defect size for the two observers was not significantly different either. Conclusion: Defects confined to spongy bone can be identified on film and PSP radiographs and CBCT scans. However, interpretation of PSP images and CBCT scans needs greater expertise and skills.